ENGLISH LANGUAGE POLITENES OF TOURIST GUIDES IN BALI - Murdana, I Ketut; Budiarsa, Made; Suastra, I Made; Mbete, Aro Meko (e-Journal of Linguistics; Vol. 8. Juli 2014 No.2)
This paper deals with the ways used by tourist guides (TG) in Bali to express their politeness to foreign tourists  (FT) through several speech acts, such as greetings the FT, welcoming the FT to Bali, introducing themselves to the FT, thanking the FT, and apologizing to the FT. The research is conducted in several tourist objects at two Regency and Municipality in Bali, which are Badung Regency and Denpasar Municipality. The research result reveals that the tourist guides employ those speech acts to express their English language politeness to the foreign tourists (FT). Those speech acts are also used to perform their friendliness in providing tour guide services to the FT.
Keywords: politeness, speech act, greetings, welcomings, introducing oneself, thankings, apologizings